Biallelic THOC6 pathogenic variants: Prenatal phenotype and review of the literature. Issue 10 (15th April 2022) - Ruaud, Lyse; Roux, Nathalie; Boutaud, Lucile; Bessières, Bettina; Ageorges, Faustine; Achaiaa, Amale; Bole, Christine; Nitschke, Patrick; Masson, Cécile; Vekemans, Michel; Verloes, Alain; Attie‐Bitach, Tania
Abstract: Background: The THOC6 protein is a component of the THO complex. It is involved in mRNA transcription, processing and nuclear export. Interestingly molecular biallelic loss‐of‐function variants of the THOC6 gene were identified in the Beaulieu–Boycott–Innes syndrome (BBIS– OMIM # 613680). This condition was described in 17 patients and is characterized by a moderate to severe intellectual disability, facial dysmorphic features and severe birth defects such as heart, skeletal, ano‐genital and renal congenital malformations. Methods: In the present study, we report on a new family with two affected sibs. The 6‐year‐old female had severe intellectual disability with autistic features, feeding difficulties, growth delay, facial dysmorphic, and congenital malformations (hand, skeletal and cardiac anomalies). The male fetus presented antenatally with a cystic hygroma associated with severe aortic and left ventricular hypoplasia. Autopsy, after termination of pregnancy at 15 weeks of gestation, showed facial dysmorphic, short right thumb and hypospadias. Results: Exome sequencing detected in both sibs compound heterozygous variants of the THOC6 gene (NM_024339.3, GRCh37): the already reported c.[298T>A;700G>T;824G>A] haplotype and a novel variant c.977T>G, p.(Val326Gly). Discussion: We made a review of the literature of 17 BBIS reported patients including our two siblings. Severe to moderate ID and congenital malformations were constant. Prenatal and postnatal failure to thrive were frequent. Brain MRI were not specific. Prenatal findings were reported in 40% of cases but we described the first case of cystic hygroma. The present study reports extends the prenatal delineation of the phenotypic features observed in association with the presence of THOC6 variants. In addition, it underscores the intrafamilial phenotypic variability observed in BBIS.